PERAN SERIKAT PEKERJA/SERIKAT BURUH DI KABUPATEN PURWAKARTA DALAM PROSES PENETAPAN UPAH MINIMUM (STUDI KASUS FEDERASI SERIKAT PEKERJA METAL INDONESIA) - Trio Setiyo Susilo; Achmad Taufiq; Lusia Astrika (Journal of Politic and Government Studies, 2015)
Minimum wage becomes a sensitive issue because it involves the welfare of labour and there is a complicated complexity. Wage issue is the most important priority of the various matters in Federation of Indonesian Metal Workers Union or worker unions else. It caused by the issue of wages become an urgency and it was like a labour as veins, so the blood is wages. FSPMI in Purwakarta has an important role in fighting for the welfare of labour.This study aimed to describe role of FSPMI in Purwakarta on minimum wage fixing process who was conducted by Wage Council in Purwakarta, in this case FSPMI has the representative in Wage Council of Purwakarta. Moreover, also described the various problems in the field such as supporting and inhibiting factors either the internal or the external, so that can be concluded extent of the FSPMI influence for the labour welfare. This study used the descriptive qualitative method. Triangulation of data or sources technique is used in this study to obtain a data validity. The primary data sources was obtained through interviews with the relevant informants and secondary data was obtained from documents, records, internet, and other sources that are related to this research.Based on these results, it can be seen that FSPMI have two alternatives in solving minimum wage, the alternatives are lobby and action. Along with the joining of FSPMI in Wage Council of Purwakarta since 2012, minimum wage increases in Purwakarta significantly occurred. In carrying out its role, FSPMI was faced with a variety of supporting and inhibiting factors either the internal or the external. FSPMI has an important meaning for the labour member if viewed from two aspects, that aspects are the purpose and benefits of joining the FSPMI. Objectives and benefits is closely related to welfare problems.Recommendations which can be given that such elements exist in the Wage Council could establish the best synergy especially the elements of workers union. When it was sitting on the Wage Council is no longer the name of the organization but it represents the aspirations of all workers in Purwakarta. Employers should not only promote the company's profits, but also must be able to create a symbiotic mutualism between employers and workers.Keywords: Workers Union, Minimum Wage, Purwakarta.